Kinetics of acid reactions: making sense of associated concepts - Tan, K.C.D.; Treagust, David; Chandrasegaran, Arulsingam; Mocerino, Mauro (The Royal Society of Chemistry, 2010)
In chemical kinetics, in addition to the concepts related to kinetics, stoichiometry, chemical equilibrium and the characteristics of the reactants are often involved when comparing the rates of different reactions, making such comparisons very challenging for students at all levels, as well as for pre-service science teachers. Consequently, four multiple-choice items were developed to determine the understanding of 217 pre-service science teachers of the kinetics of acid reactions that are taught at the Grade 9 to 10 levels in Singapore schools. Each of four items compared two different acid reactions under similar conditions, and respondents were required to select the best graphical representation for the two reactions.Respondents were also required to provide reasons to explain their particular selection for each item. In addition, one item on the dissociation of sulfuric acid and two items involving excess/limiting reagents were also included to provide additional data on the pre-service teachers’ understanding of these concepts that were assessed in the four items on kinetics of acid reactions. The results showed that the pre-service teachers had difficulties in explaining the properties of different common acids, including the dissociation of the acids and how these affect the rates of the different acid reactions. This study highlights the importance of determining pre-service teachers’ understanding of the concepts that they will be teaching with a view to addressing areas of difficulty, as these will have consequences on their future students’ learning.